(7a+9b+8)+(a-b+1)=

Simple and best practice solution for (7a+9b+8)+(a-b+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7a+9b+8)+(a-b+1)= equation:


Simplifying
(7a + 9b + 8) + (a + -1b + 1) = 0

Reorder the terms:
(8 + 7a + 9b) + (a + -1b + 1) = 0

Remove parenthesis around (8 + 7a + 9b)
8 + 7a + 9b + (a + -1b + 1) = 0

Reorder the terms:
8 + 7a + 9b + (1 + a + -1b) = 0

Remove parenthesis around (1 + a + -1b)
8 + 7a + 9b + 1 + a + -1b = 0

Reorder the terms:
8 + 1 + 7a + a + 9b + -1b = 0

Combine like terms: 8 + 1 = 9
9 + 7a + a + 9b + -1b = 0

Combine like terms: 7a + a = 8a
9 + 8a + 9b + -1b = 0

Combine like terms: 9b + -1b = 8b
9 + 8a + 8b = 0

Solving
9 + 8a + 8b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + 8a + -9 + 8b = 0 + -9

Reorder the terms:
9 + -9 + 8a + 8b = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 8a + 8b = 0 + -9
8a + 8b = 0 + -9

Combine like terms: 0 + -9 = -9
8a + 8b = -9

Add '-8b' to each side of the equation.
8a + 8b + -8b = -9 + -8b

Combine like terms: 8b + -8b = 0
8a + 0 = -9 + -8b
8a = -9 + -8b

Divide each side by '8'.
a = -1.125 + -1b

Simplifying
a = -1.125 + -1b

See similar equations:

| -2-8+a=116 | | -2x^2-3x+18= | | 5x+4=8x+3 | | -70=4(a+1)-6(6a+7) | | -6=8/x | | 6u^2-10u^5v^4/6u^3y^6 | | 8x-8+3a=5ax-2a | | n/-3.2=1.6 | | 4x+24=3x+4 | | 4c+5=z-4 | | -(-6n+6)-4(1+5n)=18 | | -5x-13=38 | | 3x+2x-6=26 | | 8+-10=6 | | 11y+77=31y+62 | | 3/10x-15 | | 4m+5-3m=x | | 1/3y=1/6 | | 280^1/2 | | 24+n=19 | | 1x+5=x-7 | | 7+5s-6=7s+7-5s | | 3-12y=7y+7 | | 4/5x-48 | | (w^9)^(1/3) | | (-6)+3.98= | | 2x^3+4x^2+4x+8=0 | | 9+9m-4=7m+45-3m | | 6(r-14)+2(r-3)=14 | | 2(3y-7)=2(3+8y) | | 2[2x-1]=18 | | 6(a-14)+5(a-18)=2 |

Equations solver categories